2009
DOI: 10.1097/hjh.0b013e32832e49a8
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular geometry and endogenous ouabain in a Flemish population

Abstract: Background Endogenous ouabain, an endogenous digitalis-like steroid, is synthesized in the adrenal glands and possibly in the hypothalamus. In vitro and in vivo, endogenous ouabain triggers growth and proliferation of cardiomyocytes.Objective We therefore investigated the association between left ventricular structure and function and plasma endogenous ouabain in a general population.Methods We randomly recruited 536 individuals from a general population (50.7% women, mean age 53.1 years). Measurements include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Subsequently, several groups were successful in the isolation and purification of two distinct classes of endogenous CS, cardenolides and bufadienolides, from multiple mammalian tissues (2,14,19,28,29). Importantly, clinical studies have identified above normal circulating levels of ouabain/digitalis-like factor in diverse pathological conditions (2,3,12,15,27,35). Circulating CS levels are strongly correlated with the extent of left ventricular (LV) remodeling and impairment of LV function, implying a definitive pathophysiological role for this new class of steroid hormones.…”
mentioning
confidence: 99%
“…Subsequently, several groups were successful in the isolation and purification of two distinct classes of endogenous CS, cardenolides and bufadienolides, from multiple mammalian tissues (2,14,19,28,29). Importantly, clinical studies have identified above normal circulating levels of ouabain/digitalis-like factor in diverse pathological conditions (2,3,12,15,27,35). Circulating CS levels are strongly correlated with the extent of left ventricular (LV) remodeling and impairment of LV function, implying a definitive pathophysiological role for this new class of steroid hormones.…”
mentioning
confidence: 99%
“…In smokers, median tobacco use was 12 cigarettes per day (interquartile range: 7-20). In regular drinkers, the median alcohol consumption was 11 g/day (interquartile range: [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Results Study Populationmentioning
confidence: 99%
“…One experienced observer (T.K.) performed all echocardiograms 10 according to the recommendations of the American Society of Echocardiography, 11 using a Vivid 7 Pro (GE Vingmed, Horten, Norway) interfaced with a 2.5-3.5 MHz phased-array probe. The observer obtained M-mode echocardiograms of the LV from the parasternal long-axis view guided by two-dimensional image.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, EO modulates Na + /K + -ATPase in the vascular bed decreases vascular compliance by increasing smooth muscle tone [7,10] and this effect is ouabain specific [11]. In the heart, EO activated though Na + /K + -ATPase generated Src-kinase second messenger pathway promotes cardiomyocyte hypertrophy [12]. Observational data in naïve hypertensive patients revealed that elevated EO concentrations are associated with increased diastolic blood pressure and left ventricular hypertrophy [13].…”
Section: Introductionmentioning
confidence: 99%